Standardized extract of Tinospora crispa stimulates innate and adaptive immune responses in Balb/c mice. Issue 3 (3rd February 2016) - Ahmad, Waqas; Jantan, Ibrahim; Kumolosasi, Endang; Bukhari, Syed Nasir Abbas
Abstract : Tinospora crispa extract exhibited immunostimulatory effects by promoting nitric oxide production ability, peritoneal macrophage phagocytosis, delayed type hypersensitivity, and enhancing serum immunoglobulins and serum lysozyme levels. Abstract : Standardized extract of Tinospora crispa has been shown to exhibit immunostimulatory effects on innate immune responses in Wistar-Kyoto rats by enhancing neutrophil and T cell-mediated immunity. In this study the immunostimulatory effects of T. crispa were further investigated on the cellular immune response by determining its effect on nitric oxide (NO) production ability, peritoneal macrophage phagocytosis and delayed type hypersensitivity (DTH), whereas the humoral immune response was evaluated through the measurement of serum immunoglobulins (IgG and IgM) and serum lysozyme levels. Male Balb/c mice were immunized with 200 μL of 5 × 10 9 sheep red blood cells (sRBCs) per mL on day 0 and orally administered with 50, 100 and 200 mg per kg of ethanol extract of T. crispa for 14 days. Syringin and magnoflorine were qualitatively and quantitatively analyzed in the extract as chemical markers by using a validated reversed-phase high performance liquid chromatography method. T. crispa extract (TCE) considerably improved the peritoneal macrophages' ability to engulf FITC-labeled E. coli in a dose-dependent manner. TCE also dose-dependently promoted NO production in peritoneal macrophages activated by a lipopolysaccharide (LPS) and markedly potentiated the sRBS-induced swelling rate of the mice paw in DTH. The extract significantly enhanced the level of serum immunoglobulins, showing maximum activity at 100 mg kg −1 . Compared to the control groups, the serum lysozyme level and myeloperoxidase (MPO) activity were significantly higher in extract-treated groups. These findings suggest that T. crispa possesses strong immunostimulatory activities and might act as a natural immunomodulator as well as a potential nutraceutical for the modulation of the immune response.